Results of clinical trial in Russia to assess immunological efficacy and safety of meningococcal vaccine (serogroups A, C, Y, W, X) in adults - I. V. Fel'dblyum; S. O. Golodnova; M. Kh. Alyeva; T. M. Repin; E. V. Gorelikova; A. S. Korovkin; E. S. Safonova; A. M. Vlasov (Эпидемиология и вакцинопрофилактика)
Relevance. The diverse serogroup composition of meningococcal pathogens circulating in different countries, the challenges in predicting serogroup prevalence, migration processes, and the active aerosol transmission mechanism of meningococcal infection necessitate the use of vaccines with the broadest possible serogroup coverage for effective prevention.Aim. To evaluate the immunological efficacy and safety of the MENVAID® vaccine for the prevention of meningococcal infections caused by serogroups A, C, Y, W, and X in the Russian Federation.Materials and Methods. The immunological efficacy and safety of the MENVAID® vaccine were assessed in a prospective, comparative, randomized, double-blind clinical trial with parallel groups involving adult volunteers aged 18 to 65 years. A total of 60 adult volunteers were randomized into two groups in a 1:1 ratio (Group I, n = 30; Group II, n = 30). The comparator vaccine was Menactra®.Study Results. For all five serogroups included in the MENVAID® vaccine, both the primary and secondary immunogenicity endpoints in adults aged 18–60 years were met in comparison to the reference product (Difference ≤10 %, GMT ratios ≥0.5, respectively), confirming that the immunogenicity of MENVAID® is non-inferior to that of the comparator vaccine, Menactra®. Moreover, MENVAID® demonstrated significantly higher GMT levels for serogroups C, Y, and W compared to the comparator vaccine. In total, 132 adverse events (AEs) were reported during the study in adults, of which 124 were related to vaccine administration and were represented by local and systemic reactions: 66 AEs were recorded in Group I participants (220 %), and 58 AEs in Group II participants (193.3 %). No statistically significant difference in the number of AEs between the groups was observed. No serious adverse events (SAEs) were reported during the study.Conclusion. The MENVAID® vaccine for the prevention of meningococcal infection caused by serogroups A, C, Y, W, and X demonstrated non-inferior efficacy and comparable safety to the comparator vaccine when administered to healthy individuals aged 18 to 60 years.